Defining CRISPR–Cas9 genome-wide nuclease activities with CIRCLE-seq. Issue 11 (November 2018) - Lazzarotto, Cicera; Nguyen, Nhu; Tang, Xing; Malagon-Lopez, Jose; Guo, Jimmy; Aryee, Martin; Joung, J.; Tsai, Shengdar
Abstract Circularization for in vitro reporting of cleavage effects by sequencing (CIRCLE-seq) is a sensitive and unbiased method for defining the genome-wide activity (on-target and off-target) of CRISPR–Cas9 nucleases by selective sequencing of nuclease-cleaved genomic DNA (gDNA). Here, we describe a detailed experimental and analytical protocol for CIRCLE-seq. The principle of our method is to generate a library of circularized gDNA with minimized numbers of free ends. Highly purified gDNA circles are treated with CRISPR–Cas9 ribonucleoprotein complexes, and nuclease-linearized DNA fragments are then ligated to adapters for high-throughput sequencing. The primary advantages of CIRCLE-seq as compared with other in vitro methods for defining genome-wide genome editing activity are (i) high enrichment for sequencing nuclease-cleaved gDNA/low background, enabling sensitive detection with low sequencing depth requirements; and (ii) the fact that paired-end reads can contain complete information on individual nuclease cleavage sites, enabling use of CIRCLE-seq in species without high-quality reference genomes. The entire protocol can be completed in 2 weeks, including time for gRNA cloning, sequence verification, in vitro transcription, library preparation, and sequencing. This protocol describes CIRCLE-seq (circularization for in vitro reporting of cleavage effects by sequencing), a sensitive and unbiased method for defining the on-target and off-target activity of CRISPR–Cas9 nucleases genome-wide.